MEDIA PEMBELAJARAN INTERAKTIF SIMULASI MENGETIK 10 JARI - Dean Alif Ahmad Dean (Fakultas Ilmu Komputer, Unversitas Muhammadiyah Riau, 2020)
Interactive Learning Media is currently in great demand and has also been widely applied to deliver subject matter both in schools and universities. Typing is one of the basic skills needed at work or school. But not everyone has the ability to type correctly using ten fingers. To measure or test the ability of someone in typing ten fingers, in this study discusses the design and manufacture of an application. This application is based on standard typing competencies on the keyboard taken from SKKNI. Test typing skills are generally carried out by professional certification bodies to provide certification or proof of one's competence. To determine the results of the exam, participants use assessment based on the certification of practical and theoretical examinations. Ratings are based on speed and accuracy in typing which are added together. Evaluation is based on understanding the theory test in typing on a standard keyboard.